Voronovskaja type theorem for the lupaş q-analogue of the bernstein operators - Mahmudov, Nazim Idrisoglu; Sabancigil, Pembe (My University, 2012)
In this paper, we estimate the third and the fourth order central moments for the difference of the Lupa ?s q-analogue of the Bernstein operator and the limit q-Lupaş operator. We also prove a quantitative variant of Voronovskaja's theorem for R n;q.. © 2012 Department of Mathematics, University of Osijek.
Keywords: Limit q-lupaş; Lupaş; Operator; q-analogue; q-bernstein polynomials; Voronovskajatype formulas